Small Structure, Large Effect: Functional Surfaces Inspired by Salvinia Leaves. Issue 9 (22nd July 2021) - Bing, Wei; Wang, He; Tian, Limei; Zhao, Jie; Jin, Huichao; Du, Wenbo; Ren, Luquan
Abstract : Nature‐inspired superhydrophobic surfaces have attracted significant attention because of their remarkable properties. In particular, recent findings about the aquatic plant Salvinia provide novel approaches for the application of superhydrophobic surfaces. The unique heterogeneous eggbeater structures endow Salvinia leaves with superhydrophobicity and strong adhesion, which ensures that the leaves show durable air‐retainability in underwater environments. However, the complex eggbeater structures present a difficult manufacturing challenge. Therefore, this review first introduces the air‐retention mechanism, which may benefit the design of Salvinia ‐inspired structures. Moreover, advanced techniques including photolithography, direct laser lithography, chemical vapor deposition, electrodeposition, electrostatic flocking, 3D printing, chemical etching, and plasma etching recently have been developed for fabricating Salvinia ‐inspired structures. This review focuses on the advantages, disadvantages, and application prospects of such techniques. In addition, the excellent air‐retainability of Salvinia structures has inspired many engineering applications, including drag reduction; water harvesting, evaporation, and repellence; oil/water separation; and thermal insulation. This review discusses the performance and challenges of artificial structures to such applications. Finally, methods of evaluating air‐retainability are discussed. It is expected that this review will not only satisfy scientific curiosity but also contribute to the design and application of Salvinia ‐inspired functional surfaces. Abstract : Advanced fabrication techniques have been recently developed to imitate the complex structures of Salvinia leaves. The excellent air‐retainability of Salvinia structures inspires many engineering applications.